Mechanisms of Stress-Induced Spermatogenesis Impairment in Male Rats Following Unpredictable Chronic Mild Stress (uCMS) - Zou, Peng (Int J Mol Sci, 2019)
The negative association between psychological stress and male fertility has been known for many years. This study was aimed at (i) identifying spermatogenesis impairment induced by psychological stress in rats and (ii) exploring the role of glucocorticoid receptor (GR) signaling in these adverse effects (if they exist). Male Sprague Dawley rats were exposed to a six-week period of unpredictable chronic mild stress (uCMS) along with cotreatment of GR antagonist RU486 (1 mg/kg/day). Testicular damage was assessed by testicular pathological evaluation, epididymal sperm concentration, serum testosterone levels, testicular apoptotic cell measurements, and cell cycle progression analyses. Rats in the uCMS group had decreased levels of serum testosterone and decreased epididymal sperm concentration. The uCMS-treated rats also had decreased numbers of spermatids and increased levels of apoptotic seminiferous tubules; additionally, cell cycle progression of spermatogonia was arrested at the G(0)/G(1) phase. Furthermore, uCMS exposure caused an increase in serum corticosterone level and activated GR signaling in the testes including upregulated GR expression. RU486 treatment suppressed GR signaling and alleviated the damaging effects of stress, resulting in an increased epididymal sperm concentration. Overall, this work demonstrated for the first time that the activation of GR signaling mediates stress-induced spermatogenesis impairment and that this outcome is related to cell apoptosis and cell cycle arrest in germ cells.